Step-by-step development of jointstock companies in Uzbekistan (Eurasian Research Bulletin, 2023)
This article examines the historical development of joint-stock companies on the territory of the Republic of Uzbekistan with a comparative analysis of the joint-stock history of other countries. During these analyses, based on scientific research in this area, it was analyzed how joint-stock companies were formed at different times and the author expressed his opinion on this issue